Trauma management therapy with virtual-reality augmented exposure therapy for combat-related PTSD: A randomized controlled trial. (January 2019) - Beidel, Deborah C.; Frueh, B. Christopher; Neer, Sandra M.; Bowers, Clint A.; Trachik, Benjamin; Uhde, Thomas W.; Grubaugh, Anouk
Highlights: Virtual-reality augmented exposure therapy is efficacious for combat-related PTSD. Virtual-reality augmented exposure therapy decreases depression and anger. Adding group therapy decreases social isolation in veterans. Treatment outcome is maintained at six month follow-up. Abstract: Virtual reality exposure therapy (VRET) realistically incorporates traumatic cues into exposure therapy and holds promise in the treatment of combat-related posttraumatic stress disorder (PTSD). In a randomized controlled trial of 92 Iraq and Afghanistan veterans and active duty military personnel with combat-related PTSD, we compared the efficacy of Trauma Management Therapy (TMT; VRET plus a group treatment for anger, depression, and social isolation) to VRET plus a psychoeducation control condition. Efficacy was evaluated at mid- and post-treatment, and at 3- and 6-month follow-up. Consistent with our hypothesis, VRET resulted in significant decreases on the Clinician Administered PTSD Scale and the PTSD Checklist-Military version for both groups. Also consistent with our hypothesis, significant decreases in social isolation occurred only for those participants who received the TMT group component. There were significant decreases for depression and anger for both groups, although these occurred after VRET and before group treatment. All treatment gains were maintained six-months later. Although not part of the original hypotheses, sleep was not improved by either intervention and remained problematic. The results support the use of VRET as an efficacious treatment for combat-related PTSD, but suggest that VRET alone does not result in optimal treatment outcomes across domains associated with PTSD.